Avaliação do potencial terapêutico da farinha da casca da passiflora eduli nas dislipidemias e diabetes induzidas - Gomes Neto, José Nilson Ferreira (2009)
The Brazilian flora has a great variety of plants with therapeutic potential for the treatment of various diseases. Much of the population using therapies based on knowledge as the first popular alternative therapy. The Passiflora edulis f. flavicarpa (Passion fruit) is an abundant natural resource in Brazil that is being used by people to control blood glucose, obesity and dyslipidemia, but without scientific evidence of such therapeutic properties. This study aimed to evaluate the effect of the aqueous suspension of Passiflora edulis (ASPE) in animals with induced diabetes and dyslipidemia. Male mice were used (30-40g), albino (Mus musculus), Swiss variety, divided into groups of six animals. The dyslipidemias were induced by fructose, and a Triton hypercholesterolemic ration (HR). The diabetes was induced by Alloxan. Repeated administration of fructose (75g/500mL and 10g/10mL) produced an increase in TG (201.7 ± 6.1 mg / dL *, * p <0.05), equivalent to one of hypertriglyceridemia 47.4% *, * p <0.05. Treatment of animals with ASPE 200mg/kg significantly reduced the increase in the 45.6% *, * p <0.05. The intraperitoneum injection of Triton in the dose of 400 mg / kg induced a significant hyperlipidemia in mice. During the experiment, at 24, there was an increase in TG (5725.0 ± 136.2 mg / dL *, * p <0.05), with a hypertriglyceridemia of 1949.8% *, * p <0.05 , while in 48 there was an increase in TG (2110.0 ± 155.1 mg / dL *, * p <0.05), equivalent to 547.2%. The administration of ASPE 100 significantly reduced the Triton induced increase in serum levels of triglycerides in 28.9% and 23.6% * (* p <0.05) at 24h and 48h, respectively. In groups that were treated with hydroalcoholic extract of Passiflora edulis (HEPE) at doses of 50, 100 and 200mg/kg reductions were not detected with statistical significance (p <0.05) in serum triglycerides. In the induction of hypercholesterolemia by feeding with HR, the positive control group showed an increase in serum cholesterol of 86.66% * (* p <0.05) while ASPE 100 in 19.27% * (* p <0. 05) the concentration of blood cholesterol. After 28 days of treatment with ASPE the liver enzymes (AST and ALT), pancreas (amylase and lipase) and creatinine were not significant changes (p <0.05) in their serum. The induction of diabetes was obtained after 48h of administration of Alloxan 150mg/kg, where there has been an elevation of blood glucose (392.2 ± 3.94 mg / dL *, * p <0.05), however ASPE 100 and 200 mg / kg did not promote statistically significant reduction (p <0.05) in glycemia. These results suggest that the flour of the bark of fruit is able to reduce levels of total cholesterol and triglycerides, where it likely hypolipidemic effect occurs at the expense of the presence of pectin in the peel. Blood glucose was not reduced significantly by the meal of fruit and its use had no influence on liver metabolism, kidney and pancreas.